O sistema de certificação do etanol brasileiro sob a ótica do princípio constitucional do desenvolvimento sustentável - Cavalcante, Hellen Priscilla Marinho (2013)
The gradual inclusion of biofuels is a necessary change that countries must include in their energy mixes. Energy sources still widely used in the world, such as oil and coal, are endowed with a high pollution load to the environment, bringing damages to the water, to the air and to humans as well. In addition, although there are conflicting studies, they are also identified as major causes of the greenhouse effect and the global warming phenomenon. They are, moreover, finite sources of energy, given that its reserves will surely run out. However, even if the introduction of biofuels, such as ethanol, in the energy mix is crucial for the survival of the present and future populations, this insertion cannot settle so disorderly and, thus, one must ensure the quality of these resources and promote transparency in international trade. In this manner, a certification process for ethanol is essential to attest that this biofuel meets the sustainable requirements defined for its production. Hence, this study sought to address the importance of the adoption of certification in the ethanol industry, according to the principle of sustainable development, by analyzing the evolution of its concept, its combination with the fundamental objectives sculptured in the Constitution of 1988, its regulation under Brazilian laws and the need for a balance between economic activities and the mentioned principle. The work also encompassed the criteria used to establish certification standards and their participating actors, combined with a study of ongoing initiatives. Finally, the consequences of the adoption of a certification process for ethanol in Brazil were presented, both in terms of sustainable development and in international trade